Recovery of the commercial sponges in the central and southeastern Aegean Sea (NE Mediterranean) after an outbreak of sponge disease - CASTRITSI-CATHARIOS, J.; MILIOU, H.; KAPIRIS, K.; KEFALAS, E. (Mediterranean Marine Science, 2011)
The distribution and biometry of commercial sponges (Porifera) in coastal areas of the central and southeastern Aegean Sea was investigated to estimate the recovery progress of the populations eight years after the first appearance of sponge disease. Signs of the disease were detected only in 1.6% of the harvested sponges. Multivariate analysis on the percentage abundance of sponges showed two distinct groups among the sixteen fishing grounds studied: the eight deep (50-110 m) and the eight shallow ones (<40 m). The group from the deep depths consisted of Spongia officinalis adriatica, S. agaricina and S. zimocca. The infralittoral zone was characterized by the presence of Hippospongia communis, S. officinalis adriatica and S. officinalis mollissima. These bath sponges showed an enhanced abundance in the eastern Cretan Sea (S. Aegean Sea). In addition, their dimensions, particularly height, increased with increasing depth. It is indicated that the hydrographic conditions prevailing in the eastern Cretan Sea affected the repopulating processes of sponge banks. In each species, the biometric characteristics of the experimental specimens were similar to those of the sponges found in the market and harvested at respective depths prior to the appearance of sponge disease.